Tindak Pidana Pencemaran Nama Baik Melalui Facebook Menurut Kuhp Dan Undang-Undang Nomor 11 Tahun 2008 Tentang ITE - Subekti, Arif Satria; Pradana, Novian Ardynata Setya; Ardhira, Ajrina Yuka; Zulfikar, Mukhammad Tismandico Ilham (Jurnal Hukum & Pembangunan, 2020)
The size of an action can be named as defaming the reputation of others is still unclear because many factors must be studied. In the case of defamation or defamation that is protected, the protection of others for the other person's point of view is protected and the agreed name in the eyes of others. Someone even the authorities will face us to account for a word that we have made against someone. Being asked to act disgracefully can help fight in the community. More than that, in solving problems, the legal people are actually required to really determine the normative, in the sense that the word to settle a criminal case must be firmly grounded in the existing legislation. In contrast to the field of Civil Law or other areas of Law, Criminal Law has a Legality Principle that discusses new actions that can be convicted if there are already written legal rules issued before the action is taken.